Sismología al alcance cotidiano de los ingenieros (2021)
Researchers from the School of Engineering created a guide so that their colleagues can carry out understandable studies adjusted to their needs when carrying out the structural design of a building in the face of seismic threats. This conceptual model is a contribution to the way of understanding the problem and approaching it.